2019
DOI: 10.1002/tox.22815
|View full text |Cite
|
Sign up to set email alerts
|

Esculetin induces cell cycle arrest and apoptosis in human colon cancer LoVo cells

Abstract: We investigated the anti‐cancer effects of ESC in human colon cancer LoVo cells. Cell counting assay results showed that ESC inhibited the proliferation of LoVo cells. Cell cycle arrest results showed that cell cycle was arrested during the G0/G1 phase in the ESC‐treated LoVo cells. Western blot results showed that the cell cycle inhibitory proteins p53, p27, and p21 were increased, and cyclin D1, the cell cycle progressive protein, was decreased. Sp1 is a transcription factor regulating cell proliferation, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…Molecular analysis of the mechanisms by which the ethanolic extract induced cell death suggested a double pathway based on apoptosis mediated by caspases and autophagy. Recent studies showed that esculetin alone inhibited proliferation in LoVo colon cancer cells, inducing arrest in the G0/G1 phase and increasing the propapoptotic proteins caspase 3, 7, and 9 [50,51]. Similar results were obtained by Wang et al [52] in leukemia cell lines, which exhibited apoptosis and autophagy after treatment with esculetin.…”
Section: Discussionsupporting
confidence: 76%
“…Molecular analysis of the mechanisms by which the ethanolic extract induced cell death suggested a double pathway based on apoptosis mediated by caspases and autophagy. Recent studies showed that esculetin alone inhibited proliferation in LoVo colon cancer cells, inducing arrest in the G0/G1 phase and increasing the propapoptotic proteins caspase 3, 7, and 9 [50,51]. Similar results were obtained by Wang et al [52] in leukemia cell lines, which exhibited apoptosis and autophagy after treatment with esculetin.…”
Section: Discussionsupporting
confidence: 76%
“…Previously, we reported that Esculetin, which is natural compound derived from Artemisia capillaris , Citrus limonia , and Euphorbia lathyris , induced cell cycle arrest and apoptosis in human colon cancer LoVo cells 51 . In that study, we showed the antiproliferative effects of Esculetin in LoVo cells, which was associated with upregulation of p53 expression.…”
Section: Discussionmentioning
confidence: 78%
“…However, in malignant cells, aberrant expression of cell cycle regulators attenuates the differentiation of cells that results in irregular cell growth. In the recent past, numerous reports have suggested that natural compounds have antiproliferative activity by triggering cell cycle arrest ( 48 ). Luo et al .…”
Section: Resultsmentioning
confidence: 99%
“…, which consists of four distinct progressive phases (subG1/G0, G1, S, and G2/M)(47).Under normal circumstances, the progression of the cell cycle is tightly regulated by a cascade activation of cyclins, cyclin-dependent kinases (CDKs), and cyclin-dependent kinase inhibitors. However, in malignant cells, aberrant expression of cell cycle regulators attenuates the differentiation of cells that results in irregular cell growth.…”
mentioning
confidence: 99%